Struggle and Hope Reflections on the recent history of the Transkeian People - Mda, Mda (African Sun Media, 2019)
Struggle and Hope is an absorbing memoir by a distinguished citizen of 'Phalo's Land', in which the memoirist Mda Mda, traces the fractious events of Transkeien history over the period from roughly the late eighteen-hundreds to the present - that is, through the momentous epochs of colonialism, apartheid and liberal-democracy.